2007
DOI: 10.1111/j.1752-7325.2007.00041.x
|View full text |Cite
|
Sign up to set email alerts
|

Risk Indicators for Missing Teeth in Working‐Age Pomeranians – An Evaluation of High‐Risk Populations

Abstract: The study supports the hypothesis that psychosocial conditions that affect health status as described in the general public health literature also have an effect on tooth loss. Strategies to prevent tooth loss may be expeditiously implemented in combination with approaches to prevent other health-related problems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
45
1
4

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(63 citation statements)
references
References 28 publications
13
45
1
4
Order By: Relevance
“…This relationship disappeared in smokers. Similar results were reported by Coelho et al (27) in that married subjects had the worst periodontal condition; our observations seem to agree with other dental outcomes (28,29). …”
Section: Discussionsupporting
confidence: 93%
“…This relationship disappeared in smokers. Similar results were reported by Coelho et al (27) in that married subjects had the worst periodontal condition; our observations seem to agree with other dental outcomes (28,29). …”
Section: Discussionsupporting
confidence: 93%
“…Similarly, individuals with low education levels or low household incomes had higher prevalence of tooth loss than did other individuals in many studies, including ones from Sweden, [25,37] Brazil, [38,39] Germany, [40] Norway, [41] the USA, [4246] Australia, [33] and Jordan. [47] One longitudinal comparative study from Brazil revealed that an increase in income inequality (measured by the Gini Index) from 1991 through 2003 led to an increase in the prevalence of both severe tooth loss (fewer than 9 remaining teeth) and loss of functional dentition (fewer than 20 natural teeth).…”
Section: Discussionmentioning
confidence: 99%
“…There is no information about the outcome (tooth loss) Jagger et al [38] 2013 Scotland Relationship with inequalities measure, without quantifying a direct effect of the exposure Jimenez et al [39] 2009 United States of America SEP assessed by a combination of income and education Medina-Solís et al [40] 2008 Mexico No information about income and education associations Moreira et al [41] 2010 Brazil SEP assessed by educational level Mundt et al [42] 2007 Germany Same sample from a previous study included in this review Pearce et al [43] 2009 United Kingdom SEP assessed by occupation Pihlgren et al [44] 2011 Sweden The article could not be assessed Rihs et al [45] 2009 Brazil No relationship with SEP Roder [46] 1975 Australia No information about income and education associations Shammery et al [47] 1998 Saudi Arabia SEP assessed by condition of the house Susin et al [48] 2005 Brazil SEP assessed by a combination of income and education Susin et al [49] 2006 Brazil SEP assessed by a combination of income and education Thomson et al [24] 2000 New Zealand SEP assessed by occupation Thomson et al [50] 2004 New Zealand SEP assessed by occupation Thomson [3] 2012 New Zealand SEP assessed by occupation Wennström et al [51] 2013 Sweden SEP assessed by a combination of income and education; sample composed only by women The meta-analysis considering the crude association between income and tooth loss revealed a pooled effect of OR 2.52 (95%CI 2.11-3.01) for those subjects from lower income level (Fig. 3).…”
Section: Studymentioning
confidence: 98%